Ginjal tapal kuda dengan hidronefrosis unilateral sekunder akibat atresia ureter: laporan kasus - Putu Kurnia Darma Pratama; Gede Wirya Kusuma Duarsa; Gusti Ayu Putu Nilawati; Pande Putu Yuli Anandasari (DiscoverSys Inc., 2019)
Background: Total prevalence of multiple congenital anomalies (MCA) was 15.8 per 10,000 births. Genitourinary anomalies were associated with MCA cases about 43.8% of the cases. The horseshoe kidney is one example of genitourinary anomalies related to the high incidence of MCA and up to one third also had hydronephrosis thought to be secondary to ureteric atresia.Case: A 10-month-old boy presented with a 5-month history of abdominal distention. On physical examination, there was a large non-tender cystic mass in the right upper abdomen extending down to the right lower abdomen. The other congenital anomalies on this patient were hydrocephalus, hypospadias, and bilateral undescended testis. Abdominal CT showed a significant right hydronephrosis with megaureter and mesenteric cyst. The horseshoe kidney was unclear. The surgical approach to the kidney was via a transverse upper abdominal transperitoneal incision. Exploration revealed a horseshoe kidney with cystic mass situated retroperitoneally on the right side, massive dilatation of renal pelvis and proximal ureter 3 cm from UPJ. The distal ureter was markedly atresia. It was decided to perform nephroureterectomy on the right side considering its thin renal cortex. The postoperative average urine production is 25 ml/hour, no bleeding from surgical wound, BUN 10.7 mg/dL, and serum creatinine 0.37 mg/dL.Conclusion: The horseshoe kidney is one example of genitourinary anomalies related to the high incidence of MCA. Up to one third with horseshoe kidney had hydronephrosis secondary to ureteric atresia, which can be managed by reconstruction surgery or nephroureterectomy considering the function of the affected side of kidney.Â